Comparison of flat-sheet and spiral-wound negatively-charged wide-pore ultrafiltration membranes for whey protein concentration. (May 2016) - Arunkumar, Abhiram; Molitor, Michael S.; Etzel, Mark R.
Abstract: This work compared laboratory-scale flat-sheet and pilot plant-scale spiral-wound wide-pore, negatively-charged ultrafiltration membranes for concentration of whey proteins. By placing a negative charge on the surface of ultrafiltration membranes, a wider pore size could be used to concentrate whey proteins because negatively-charged proteins were rejected by electrostatic repulsion and not simply sized-based sieving. Negatively-charged 100 kDa regenerated cellulose membranes had an 85% higher flux than unmodified 10 kDa membranes, and equivalent protein retention. The pilot plant-scale spiral-wound membranes had 70-fold more area, and a different membrane geometry than the laboratory-scale flat-sheet membranes, yet both membranes were successful in retaining >98% of the whey protein.